PENGARUH SERTIFIKASI HALAL DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK MIXUE DI PALEMBANG - Erdiansyah, Erdiansyah; Nabila, Nabila; Julaini, Julaini; Sari, Dwi Indah (Universitas Nusa Cendana, 2024)
This study aims to analyze the influence of halal certification and brand image on purchasing decisions on Mixue products. This study employs a quantitative methodology. A non-probability purposive sampling method was used to collect samples. This research was conducted by distributing questionnaires to 100 respondents who had purchased Mixue products at least once. The results of the research were carried out using classical assumption tests, which include normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analyses, determination coefficient analyses, t-tests, and F-tests. The results of the research show that, partially, there was a significant influence between halal certification and brand image on purchase decisions. And simultaneously, there is a significant influence between halal certification and brand image on purchasing decisions. The value of the R-squared determination coefficient indicated that the independent variable contributed as much as 66.1% of the dependent variable. Keywords: Halal Certification; Brand Image; Purchase Decision